Next steps of the Livestock NAMA in Costa Rica: Synthesis of stakeholder consultations and rapid assessment of their current status - Chacón, Mauricio; Segura, Jorge; Jenkins, Agripina; Fallas, Marco; Villanueva, Diego Obando Cristóbal; Chacón-Cascante, Adriana; Abarca, Sergio; Ordoñez, Jenny C.; Farnworth, Cathy Rozel; Arango, Jacobo; Rosenstock, Todd S. (2015)
Livestock NAMA in Costa Rica aims to transform the livestock production sector to achieve ecocompetitive livestock farming. n Public-private-academic partnerships evaluate and co-develop the technical and institutional building blocks of the NAMA. n The key components of NAMA development in its first pilot phase (2013-2021) are well on the track to develop a robust proposal for scaling out and implementation of the goals proposed by 2030.